Spermiogenesis and sperm ultrastructure of Cyathocephalus truncatus (Pallas, 1781) Kessler, 1868 (Cestoda: Spathebothriidea) - Brunanská, Magdaléna; Scholz, Tomás; Dezfuli, Bahram S; Poddubnaya, Larisa G (The Journal of parasitology, 2006)
Spermiogenesis and sperm ultrastructure of adult Cyathocephalus truncatus, a member of presumably basal group of "true" cestodes (Eucestoda), have been examined for the first time by using transmission electron microscopy. The process of sperm formation corresponds in basic pattern to that of the Pseudophyllidea. In addition, the 2 pairs of electron-dense attachment zones are present in median cytoplasmic process of C. truncatus. However, mature spermatozoa of C. truncatus differ significantly from those of the pseudophyllideans, especially in the morphology of the proximal and distal spermatozoon extremities. The proximal extremity of the mature spermatozoon lacks a crested body, which is present in more derived cestodes and some pseudophyllideans. The distal end of the mature spermatozoa exhibits different morphology in the gametes from testes and those from receptaculum seminis. New for the Eucestoda is a finding that a lateral cytoplasmic extension creates the distal end of the spermatozoa from testes, resembling sperm of some Monogenea and Digenea. In contrast, the distal extremity of the spermatozoa from receptaculum seminis contains only a nucleus. Despite the above-mentioned peculiarities, the ultrastructural data on sperm/spermiogenesis suggest close relationships of the Spathebothriidea and Pseudophyllidea.
Keywords: nemoci ryb; spermie; Cestode Infections; Spermatogenesis; Salmonidae; testis; Fish Diseases; Itálie; zvířata; Testis; Male; cestodózy; spermatogeneze; Rusko; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Russia; Spermatozoa; Animals; Italy; mužské pohlaví; Cestoda